Chief Executive Officers and Bankruptcy Risk: Evidence from Quoted Resources Firms in Nigeria (Journal of Management and Social Sciences, 2021)
Despite the growing interest in the role of chief executive officers in their companies’ bankruptcies, very few studies have examined the nexus between chief executive officers and bankruptcy risk in Nigeria. This paper interrogates whether or not chief executive officers influence financial distress among quoted resources corporations. Data were obtained from Machameratios, a corporation which specializes in data mining for a period of 10 years (2010-2019). The data were subject of descriptive statistics such as number of observations, minimum mean, maximum mean, average mean, standard deviation and inferential statistics such as correlation matrix and multiple regression based on random effect model, which was arrived at after conducting Hausman specification check. Diagnostic checks such as normality, multicollinearity, heteroskedasticity and Breusch and Pagan Lagrangian multiplier test for random effects were carried out before arriving at decisions. Findings showed that both chief executive officers’ duality, nationality, gender, and turnover are not significant. However, the paper found chief executive officers’ tenure significant and positive and ownership to be negative but significant. As a result of these findings, it was suggested that the tenure of CEOs should be elongated while the percentage of their shares ownerships should be reduced.